KLOEPFER W; SPARBER PG - KLOEPFER W; SPARBER PG (Tufts Archival Research Center, 2007)
Confidential; Letter from Peter Sparber and William J. Kloepfer to Samuel D. Chicolte Jr. regarding his comments and recommendations related to operation down under. Identifies the two main strategies of the program as reducing the public debate over smoking and seeking to ensure the voluntary accommodation of smokers. Provides several recommendations, such as changing their policy from total opposition of smoking restrictions to accommodation of smokers, reducing the budget and asking organizations to sign the Operation Down Under advertisements among others.